Shattering the glass ceiling for women in gardening and landscaping: a mini-review - Sdao, Anna Elisa; Zeller, Sharon; De Lucia, Barbara (Frontiers in Horticulture, 2024)
The history of gardening and landscaping has historically been a male monopoly, and until the 20th century, women couldn't get anywhere near a career in these fields. This brief review focuses on some of the women who paved the way in Europe and the US and also attempts to tell some lesser-known stories, focusing on those who turned to gardening and landscaping, subjects that have been much less explored in floriculture. This review does not claim to be exhaustive, although it does attempt to draw attention to a historical period between the Victorian age and the present day. Women’s significant contributions range from the dissemination, teaching, research, education, association and popularization of gardening and landscaping. In the following, the authors briefly discuss, in the XXIth century, regarding men and women who may have similarities in education and work experience, but these similarities do not lead to comparable careers or positions in academic departments. Some scientific studies that have an impact on the design and sustainable management of green spaces linked to ecosystem services are considered. Finally, the contribution of women in landscape architecture is briefly examined.